2021
DOI: 10.3389/fonc.2021.580545
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Characteristics and Prognosis of Signet Ring Gastric Cancer: A Population-Based Study

Abstract: BackgroundTo better define the clinicopathologic characteristics of signet ring cell (SRC) gastric cancer and build a prognostic model for it.MethodsSRC patient information from 2010 to 2015 were identified using Surveillance, Epidemiology, and End Results (SEER) database. Kaplan-Meier method and log-rank test were used to estimate Overall survival (OS) and to determine associations with histologic subtypes. In COX proportional hazards regression model–based univariate and multivariate analyses, significant va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 23 publications
2
11
0
Order By: Relevance
“…al show that GSRCC occurs more frequently in the middle and lower stomach region and that GSRCC is more likely to have bone metastasis (in comparison to other gastric cancers, which tend to have liver and lung metastasis). Importantly, the study found that signet ring cancer cell histology is not independently associated with mortality when disease stage is controlled for, in which case signet ring cell carcinoma is not more aggressive than differentiated cancers (32).…”
Section: Clinicopathological Characteristics Prognosis and Treatmentsmentioning
confidence: 85%
See 2 more Smart Citations
“…al show that GSRCC occurs more frequently in the middle and lower stomach region and that GSRCC is more likely to have bone metastasis (in comparison to other gastric cancers, which tend to have liver and lung metastasis). Importantly, the study found that signet ring cancer cell histology is not independently associated with mortality when disease stage is controlled for, in which case signet ring cell carcinoma is not more aggressive than differentiated cancers (32).…”
Section: Clinicopathological Characteristics Prognosis and Treatmentsmentioning
confidence: 85%
“…Another recent study reevaluates GSRCC clinicopathological data (32) in order to attempt to clarify some of the more controversial findings, including some of those discussed in this text. The study brings solid evidence to further support that there are distinct features that separate GSRCC from gastric adenocarcinoma.…”
Section: Clinicopathological Characteristics Prognosis and Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…GSRC tended to occur in young and female patients, which was consistent with previous studies[ 9 ]. Although gastric cancer was considered to be a disease more frequently seen in men, a large number of studies had shown that the incidence of GSRC in women was higher[ 13 ]. At the same time, the age of onset of GSRC was significantly earlier than that of gastric adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have showed that the prognosis of early SRC is good, while the prognosis of advanced stage SRC is poor[ 9 , 12 ]. Most recently, abundant evidence in the United States suggested that GSRC was not necessarily a risk factor affecting prognosis[ 13 ]. Combination of postoperative adjuvant radiotherapy, chemotherapy, and targeted therapy had an excellent effect in improving the survival rate of gastric cancer patients.…”
Section: Introductionmentioning
confidence: 99%